Relationship between isokinetic strength, flexibility, and flutter kicking speed in female collegiate swimmers - Mookerjee, S.; Bibi, K. W.; Kenney, G. A.; Cohen, L. (The Journal of Strength and Conditioning Research, 1995)
The actual role and effect of kicking in crawlstroke still has not been determined exactly. Differing reports have emerged over the last 30 years. However, it is generally believed that kicking efficiency is determined to a great extent by flexibility in the ankles. Female collegiate swimmers (N = 12) performed one 25 yd and one 50 yd flutter kicking time-trial using a kicking board. Isokinetic peak torques were measured at 2.88, 6.28, and 7.85 rad/sec. Plantar and dorsi flexion measures of the ankles as well as sit-and-reach flexibility were assessed. An underwater film analysis of six Ss was used to provide a measure of the angular velocity of the downbeat phase of the kick. No measures of ankle flexibility correlated with kicking speed. However, the sit-and-reach test was correlated with the time for the longer 50 yd time-trial. Torques generated at 6.28 rad/sec were correlated with the short distance time-trial (r = .82) and to a lesser extent with the longer distance time-trial (r = .70). Underwater film analysis showed that the downbeat phase was close to 6.4 rad/sec in speed, almost the same as the torque speed that correlated with the two time-trials. These data suggest that velocity-specific flutter-kick testing and training should be done at high (sprint-speed) velocities. Implications: This study showed that kicking speed is only related to physical parameters over short distances (25 yd). The relationship is reduced with longer distances. The major variable associated with short-distance power kicking is leg speed. Peak-velocity kicking could be trained using isolated kicking drills. There does not appear to be much value in slow kicking for training other than as a recovery/rest activity. As with many aspects of human physical performance, capacities are specific to the demands of a task and specific training is the best way of developing them.